2007
DOI: 10.1007/s00299-007-0442-4
|View full text |Cite
|
Sign up to set email alerts
|

Embryogenesis and plant regeneration of hot pepper (Capsicum annuum L.) through isolated microspore culture

Abstract: We report high frequencies of embryo production and plant regeneration through isolated microspore culture of hot pepper (Capsicum annuum L.). Microspores cultured in modified NLN medium (NLNS) divided and developed to embryos. Globular and heart-shaped embryos were observed from 3 weeks after the beginning of culture, and many embryos reached the cotyledonary stage after 4 weeks of culture. These cotyledonary embryos developed to plantlets after transfer to solid B5 basal medium. We also optimized conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 45 publications
4
61
1
4
Order By: Relevance
“…The most frequently measured whorls have been corolla (Dunwell 2010) and calyx, where the ratio between calyx and corolla has been the most used parameter (Koleva-Gudeva et al 2007;Ltifi and Wenzel 1994;Mityko et al 1995;Nowaczyk and Kisiala 2006). Other authors opted for a direct estimation of the degree of purple antocyanin pigments that anthers of many pepper types accumulate during their development (Regnet 1994;Kim et al 2008;Kim et al 2004) or by a combination of this marker with the calyx/corolla ratio (Barany et al 2005;Barany et al 2010;Buyukalaca et al 2004;Dumas de Vaulx et al 1981;Supena et al 2006b;Supena et al 2006a;Ercan et al 2006;Lantos et al 2009). From these reports it can be concluded that there is no a wide consensus with respect to the most suitable marker to define which pepper flower buds should be used to maximize the percentage of VM and YBP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently measured whorls have been corolla (Dunwell 2010) and calyx, where the ratio between calyx and corolla has been the most used parameter (Koleva-Gudeva et al 2007;Ltifi and Wenzel 1994;Mityko et al 1995;Nowaczyk and Kisiala 2006). Other authors opted for a direct estimation of the degree of purple antocyanin pigments that anthers of many pepper types accumulate during their development (Regnet 1994;Kim et al 2008;Kim et al 2004) or by a combination of this marker with the calyx/corolla ratio (Barany et al 2005;Barany et al 2010;Buyukalaca et al 2004;Dumas de Vaulx et al 1981;Supena et al 2006b;Supena et al 2006a;Ercan et al 2006;Lantos et al 2009). From these reports it can be concluded that there is no a wide consensus with respect to the most suitable marker to define which pepper flower buds should be used to maximize the percentage of VM and YBP.…”
Section: Introductionmentioning
confidence: 99%
“…Anther cultures have been used in a number of cultivars with relative efficiency (reviewed in Irikova et al 2011;Seguí-Simarro et al 2011), but successful application of microspore cultures has only been reported in few hot (asian) pepper types (Kim et al 2008;Supena et al 2006b). Nevertheless, the stages most sensitive to inductive treatments in pepper revolve around the VM and YBP (Irikova et al 2011), exactly the same described for most of the known inducible species.…”
Section: Introductionmentioning
confidence: 99%
“…Media containing NAA had short and thick roots while these were medium long and thick on media containing IBA (Plate 2 and Table 5). Optimum root induction was reported by Kim et al, (2008) by sub-culturing the capsicum shoots on MS medium with NAA 0.3 mg/l. Kumar et al, (2012) observed 100% rooting when elongated shoots were transferred to MS medium supplemented with NAA at 0.5mg/l.…”
Section: Resultsmentioning
confidence: 99%
“…The authors pointed out three key factors that positively affect embryogenesis: pretreatment of microspores in sucrosefree starvation medium at 32 °C, culture in modified NLN medium (NLNS) supplemented with sucrose, and optimal microspore density at 8 × 10 4 -10 × 10 4 /mL. Lantos et al (2009) optimized the method by co-culturing pepper anthers with wheat ovaries; however, the regeneration frequency was lower (0.0 to 1.25 plants/petri dish) than in Kim et al (2008). Later experiments conducted with sweet pepper aimed to improve the effectiveness of microspore culture through optimization of culture medium, plant growth regulators, and additives (Lantos et al, 2012;Cheng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Using this method, Supena et al (2006) reported that only 0.1 plants regenerated per flower bud. Kim et al (2008) suggested a different protocol for microspore culture leading to a higher frequency of embryo production and plant regeneration (4 plants/flower bud). The authors pointed out three key factors that positively affect embryogenesis: pretreatment of microspores in sucrosefree starvation medium at 32 °C, culture in modified NLN medium (NLNS) supplemented with sucrose, and optimal microspore density at 8 × 10 4 -10 × 10 4 /mL.…”
Section: Introductionmentioning
confidence: 99%